2016
DOI: 10.3390/f7080168
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Biological Properties of Soil under Decaying Wood in a Tropical Wet Forest in Puerto Rico

Abstract: Abstract:Decaying wood is related to nutrient cycling through its role as either a sink or source of nutrients. However, at micro scales, what is the effect of decaying logs on the physical, chemical, and biotic characteristics of the soil underneath? We took samples from a 0 to 5 cm depth under and a 50 cm distance away from decaying logs (Dacryodes excelsa and Swietenia macrophylla) at 2 stages of decay, and measured soil temperature, total and available nutrients, and root length in a tropical wet forest. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 62 publications
0
27
2
Order By: Relevance
“…Unlike the studies by Zalamea et al [22] and Bantle et al [1,2], we did not find differences in soil % C or % N between tree species. One of our tree species was shared with the Zalamea et al study (D. excelsa) while our G. guidonia is in the same family and is nearly indistinguishable in quality from S. macrophylla that was used in Zalamea et al [22,23].…”
Section: Effects On Soil Nitrogen and Carboncontrasting
confidence: 57%
See 2 more Smart Citations
“…Unlike the studies by Zalamea et al [22] and Bantle et al [1,2], we did not find differences in soil % C or % N between tree species. One of our tree species was shared with the Zalamea et al study (D. excelsa) while our G. guidonia is in the same family and is nearly indistinguishable in quality from S. macrophylla that was used in Zalamea et al [22,23].…”
Section: Effects On Soil Nitrogen and Carboncontrasting
confidence: 57%
“…Soil samples collected at two depths beneath the fallen logs were spatially and temporally paired with samples collected 20-50 cm away. This study on the western side of the Luquillo Mountains was conducted when the hurricane-felled logs were 0.6-1.1 and 9.6-11 years after treefall in the two hurricane cohorts, respectively, and was a precursor to a separate study on the eastern side of the Luquillo Mountains by Zalamea et al [22,23] when their logs had decayed 6 and 15 years. This study differs in that soils were collected from 0-10 and 10-20 cm depths versus 0-5 cm in Zalamea et al [22,23], and we used the chloroform fumigation-incubation method [36] to estimate soil microbial biomass C rather than substrate induced respiration technique [37] used in Zalamea et al [22].…”
Section: Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in wet mid-elevation forests in Puerto Rico have shown that tree roots change their foraging patterns depending on relative availability of resources. Zalamea et al [111] found that soil under decaying wood had fewer roots and lower nitrate and magnesium concentrations than paired samples collected 50 cm away from the logs. Lodge et al [112] found that root abundance under versus away from logs changed seasonally, likely due to shifts in relative nutrient availability.…”
Section: Biotic Changes and Interactions In The Detrital Food Web Affmentioning
confidence: 99%
“…In the soil, Huang et al [85] used 13 C-labeled litter and showed the exotic earthworm P. corethrurus facilitated soil respiration by stimulating microbial activity; however, this effect was suppressed possibly due to the changes in the microbial activities or community when coexisting with the native worm O. borincana. Macroarthropod activity in decomposing wood may have especially strong effects on both wood decomposition [35,95] and nutrient cycling in the soil beneath the logs [99,[109][110][111]. Zimmerman et al [109] found that soil microbial biomass increased beginning 5-7 months after hurricane Hugo, corresponding to the disappearance of soil nitrate via nutrient immobilization and slowing of canopy closure in plots where woody debris was left on the forest floor, whereas soil microbial biomass was lower, soil nitrate levels were higher, and canopy closure was more rapid in plots from which debris was removed.…”
Section: Biotic Changes and Interactions In The Detrital Food Web Affmentioning
confidence: 99%